2014
DOI: 10.1007/s00414-014-0988-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA survival and physical and histological properties of heat-induced alterations in burnt bones

Abstract: During forensic casework, it is vital to be able to obtain valuable information from burnt bone fragments to ascertain the identity of the victim. Here, we report the findings of an experimental study on burnt bovine compact bone segments. Compact bones were cut to size and heated in an electric furnace at a temperature range of 100–1,100 °C with 100 °C increments. Heat-induced alterations to the bone color,weight, volume, and density were monitored using gross morphology and micro-focus X-ray computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 35 publications
4
41
0
3
Order By: Relevance
“…Numerous studies are to be found in the literature based on vibrational spectroscopy techniques, namely Raman (34,39,(61)(62)(63) and Fourier transform infrared (FTIR) (28,34,35,46,50,54,64), X-ray powder diffraction (XRD) (33,50,57,59,(65)(66)(67), X-ray fluorescence (XRF) (37,38,(68)(69)(70), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) (43,55,57,71), scanning electron microscopy (SEM) (15,43,57,(72)(73)(74)(75), nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) (15,76), and computational tomography (CT) (77)(78)(79).…”
Section: Methodologiesmentioning
confidence: 99%
“…Numerous studies are to be found in the literature based on vibrational spectroscopy techniques, namely Raman (34,39,(61)(62)(63) and Fourier transform infrared (FTIR) (28,34,35,46,50,54,64), X-ray powder diffraction (XRD) (33,50,57,59,(65)(66)(67), X-ray fluorescence (XRF) (37,38,(68)(69)(70), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) (43,55,57,71), scanning electron microscopy (SEM) (15,43,57,(72)(73)(74)(75), nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) (15,76), and computational tomography (CT) (77)(78)(79).…”
Section: Methodologiesmentioning
confidence: 99%
“…Найбільш складною вважається судово-медична експертиза ідентифікації за спаленими кістковими рештками, коли відомі методи діагностики стають неприйнятними. Окремі автори намагались визначити температурні режими, внаслідок яких ще вдається провести ДНК ампліфікацію [1,2,3]. Встановлено, що вже після спалювання при температурі 210°С, протягом 2 годин чи навіть впродовж 45 хвилин при температурі 200°С ДНК виділити не вдається.…”
Section: вступunclassified
“…Колосової (табл. 3,4,5). 16,40-36,00 11,20-27,20 12,00-32,00 11,60-31,20 13,60-35,20 24,09 18,54 19,51 19,49 21,39 2,80-7.20 2,00-5,20 2,00-6,40 2,00-6,00 2,40-6,00 4,62 3,70 3,75 3,55 3,86 Таблиця 2 Показники кількості кісткових лакун на площі 10000мкм 2 , у золі кісток людини і тварин 8,0 8,0-9,6 9,7-11,6 11,7-13,0 13,0 Висновки Проведене комплексне остеоскопічне, мікроскопічне, мікроостеометричне і мікрорентгенографічне дослідження спалених до сірого розжарювання кісток людини і окремих свійських тварин різного ступеня руйнування (від крупних фрагментів до власне золи).…”
Section: результати та їх обговоренняunclassified
“…Since the color of the bone surface varies with exposure temperature, many researchers have attempted to find a correlation between bone color and burning temperature in order to establish an index for estimating the exposure temperature of questioned bone samples. [1][2][3]5,6,9,11,12,[27][28][29][30][31][32] The degree of bone coloration also varies with burning time, and a long period of burning results in more severe color alteration. 3,28 Anaerobic burning conditions delay the coloration process.…”
Section: Coloration Of Burnt Bonesmentioning
confidence: 99%
“…[1][2][3]5,6,9,11,12,[27][28][29][30][31][32] The degree of bone coloration also varies with burning time, and a long period of burning results in more severe color alteration. 3,28 Anaerobic burning conditions delay the coloration process. 3 The soft tissues of a corpse act as a physical barrier against the flames at the start of combustion and keep bones in anaerobic conditions.…”
Section: Coloration Of Burnt Bonesmentioning
confidence: 99%